THE CONCEPTUAL METAPHOR IN KOREAN POEM 'INDONESIA INMIN-EGE JUNEUN SI [인도네시아]' BY PARK INHWAN: COGNITIVE SEMANTIC ANALYSIS: METAFORA KONSEPTUAL DALAM PUISI BERBAHASA KOREA “INDONESIA INMIN-EGE JUNEUN SI” [인도네시아 인민에게 주는 시]’ KARYA PARK INHWAN: ANALISIS SEMANTIK KOGNITIF - Lia Amelia Nurkhazanah; Tajudin Nur (Jurnal Kata, 2022)
This study aims to find out the metaphors in the poem entitled ‘Puisi buat Rakyat Indonesia' / 'Indonesia Inmin-ege Juneun Si [인도네시아 주는 시] by Park Inhwan. The method of this research was descriptive qualitative. The theory used was the cognitive semantics of conceptual metaphor according to Lakoff and Johnson (2013); image schema according to Cruse and Croft (2004). The results show that the types of metaphors are divided into 12 structural metaphors with 2 conceptual meanings of stolen and extermination; 1 conceptual meaning contains severe colonialism, natural wealth, stolen, bad condition, owned, independence, colonize, slump, and feels beautiful; 4 orientational metaphors with conceptual meaning of being independent country, colonized, oppressed, and lost in the war; and 12 ontological metaphors with conceptual meanings of tortured, loss of hope for the future, surrender, religion, tactics, independence, joint attacks, blaze of spirit, torture, hereditary, taking many victims, and victory. The schematic images are force subtheme compulsion, counterforce, restraint, and enablement; the unity image scheme subtheme part & whole and merging; existence image schema subtheme object, process, and cycle; space image scheme, up & down; scale image schema subtheme paths; the identity image scheme subtheme matching.